Silver Compounds for Caries Management - Grace Y. Xu; Irene S. Zhao; Christie Y.K. Lung; Iris X. Yin; Edward C.M. Lo; Chun Hung Chu (Elsevier, 2024)
Silver metal and compounds have antibacterial properties, although their action's mechanisms are not fully understood. Scientists generally consider that silver disrupts the bacterial cell wall. It causes a structural change in the bacterial cell membrane and cytoplasm. It also stops deoxyribonucleic acid replication, resulting in inactivating enzymatic activity and cell death. The antimicrobial effect of silver-containing compounds relies on the release of bioactive silver ions. Hence, silver metal and compounds have been used in medicine to prevent infection for hundreds of years. Silver metal and compounds are also used as antibacterial agents in dentistry. Studies have shown that silver compounds are effective in the management of dental caries. Fluoride-containing silver compounds have been found in experiments to be beneficial at remineralising dental cavities. Silver diamine fluoride (SDF) can assist in preventing and arresting tooth cavities. The World Health Organization included SDF in its Model List of Essential Medicine for both adults and children in 2021. Clinicians also use SDF to manage dentine hypersensitivity as well as to inhibit growth of periodontal pathogens. However, traditional silver compounds cause tooth discolouration because of the silver-staining effect. These side effects of their applications depend on the amount applied and the frequency of application. Researchers are developing nanosilver fluoride and silver nanoparticles to overcome the staining. This review gives an overview of the antibacterial mechanism of silver compounds, namely silver nitrate, silver fluoride, SDF, silver nanoparticles, and nano silver fluoride for caries management. The outlook for the future development of silver compounds will be discussed.